Talent management for organisational performance development in Bangladesh private industry context - Islam, Md Asadul; Jantan, Amer Hamzah; Rahman, Md Adnan; Abdul Hamid, Abu Bakar; Mahmud, Fariha; Hoque, Ashikul (Macrothink Institute, 2018)
The primary objective of this study is to identify the challenges of talent management (TM) practices within private organisations in Bangladesh. This explorative study used unstructured interview methods for the data collection. This study conducted only ten interviews including seven experts from the private sector of Bangladesh and three scholars from reputed universities of the country. After a sequential analysis of all the transcripts of the interviews, four main areas have been identified as the main challenges for talent management practices and performance development in Bangladeshi private organisations: (1) high expenditure; (2) lack of government support; (3) poor awareness; and (4) very few skilled trainers. This study includes a discussion on how TM can be applied in Bangladesh for the development of organisational performance.